2017
DOI: 10.1177/1049731517702745
|View full text |Cite
|
Sign up to set email alerts
|

What Works for Adolescent Black Males at Risk of Suicide

Abstract: We reviewed the controlled studies that report outcome findings for Black adolescent males 24 years of age and younger at risk of suicide. Our review identified 48 articles published from 2000 to 2015, 33 that met our initial criteria for full-text articles review, resulting in 6 that met all inclusion criteria. We sought to understand what works for Black males experiencing suicide ideation or engaging in suicidal behaviors (e.g., attempts). We identified crossover effects for multisystemic therapy for reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…They, however, mentioned that crossover effects for multisystemic therapy for reducing the risk for suicide ideation and attempts in Black males might exist. Their review paper suggested that attachment-based family therapy is salient for use as a clinical practice component for Black children and youth treated for STBs [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…They, however, mentioned that crossover effects for multisystemic therapy for reducing the risk for suicide ideation and attempts in Black males might exist. Their review paper suggested that attachment-based family therapy is salient for use as a clinical practice component for Black children and youth treated for STBs [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…They, however, mentioned that crossover effects for multisystemic therapy for reducing the risk for suicide ideation and attempts in NHB males might exist. That paper suggested that attachment-based family therapy is an important element of NHB males’ suicide prevention [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with White Americans, African Americans report more reasons for choosing not to kill themselves, and score higher on measures of survival and coping beliefs, and measures of moral objection to suicide (Morrison & Downey, 2000). In addition, some still hold conventional, yet refuted, beliefs that suicide is rare among African Americans (Joe et al, 2018). Third, racial differences have been noted among caregivers of individuals with physical health issues and mental illnesses (Janevic & Connell, 2001;Steuve et al, 1997).…”
Section: Study Data Analysis Was Informed By Grounded Theory Methodomentioning
confidence: 99%